The Influence of Employee Competency in Small and Medium Business Brazil and Brics and Jair Bolsonaro’s 1st Year of Presidency (International Journal of Criminology and Sociology, 2021)
This study aims to look at employee competency with job satisfaction as an intervening variable at small and medium business (SMB) by consdring the Brazil politics. The political stage in Brazil changed course towards the “right” on 1 January 2019 when the anti-globalist former army officer Jair Bolsonaro was inaugurated as the 38th President of the Republic. That was an abrupt change of ideologies for a country leaded by the “left” (Workers’ Party) in the last 13 years. Scholars made contradictory assumptions about the future of BRICS: one of the most significant economic organisations on the international arena nowadays, within the new Brazilian background. In the beginning of 2019 the opportunity for Braxit was not excluded, although there was no immediate call for it. However, the most common opinion came from pragmatists like N. Muhandiram: they affirmed that the union would keep functioning but it would meet multiple challenges. This article gives an answer to the question why the “right” turn in Brazil affects the relations between the biggest Latin American democracy and BRICS.